The Relevance of Truce: From antiquity until today - Κοκκίνη, Βίκυ (Πανεπιστήμιο Πελοποννήσου, 2014)
Truce has been a main concern from the 8th century BC until today. It is a human need to create concepts set as rules to prevent distraction. But it is also a human need to create chaos and battle fields so as to defend rights and ideas. In a world without flags and nations, humanity has nothing to divide or distribute. But from antiquity until today people have been educated to promote nationalism and patriotism. The boundaries of what belongs to whom is set by those in power and usually has nothing to do with honourable actions, but rather financial benefits and world power in leadership. However, the victims of such actions are not usually the ones to blame. It will be shown that Truce in antiquity had a different role from that which its presentday advocates are trying to achieve. Moreover it will be shown that, although sport in general promotes competition, this is not the same as conflict, and that the Olympic Games today can be used as a platform to achieve a Truce Treaty. An analysis of the opportunities and threats of this platform will be presented and discussed. This thesis will try to analyze the relevance of Truce from antiquity until today, how it is related to the Olympic Games and how the Games can play a significant role in the achievement of Truce. . Think of silence … A moment when all actions stop, and the mind finds time to think in peace. This is what Truce really is.
Keywords: Olympics - Philosophy; Olympic movement; Truce; Ολυμπιακοί αγώνες - Φιλοσοφία; Ολυμπιακό κίνημα; Εκεχειρία; Olympic truce; Olympic torch; Ολυμπιακή εκεχειρία; Ολυμπιακή φλόγα